Review of Some Identities Involving Basic Hypergeometric Series - Pant, Ghanshyam (Api Journal of Science, 2025)
In this paper, we review and verify several identities involving basic hypergeometric series including the q- binomial theorem. These identities play a fundamental role in the theory of q-series and may serve as a useful reference for beginners interested in this area of mathematics.